2017
DOI: 10.2147/nsa.s145891
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface organic coatings of cellulose nanocrystals on the viability of mammalian cell lines

Abstract: Cellulose nanocrystals (CNCs) have emerged as promising candidates for a number of bio-applications. Surface modification of CNCs continues to gain significant research interest as it imparts new properties to the surface of the nanocrystals for the design of multifunctional CNCs-based materials. A small chemical surface modification can potentially lead to drastic behavioral changes of cell-material interactions thereby affecting the intended bio-application. In this work, unmodified CNCs were covalently deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Nanoparticle surface coatings can impact both cytotoxicity and immunogenicity of nanosized biomedical materials [33]. We recently showed that CNCs-β-CD was not cytotoxic to mouse monocyte cells (J774A.1) and human breast adenocarcinoma cells (MCF-7) [21]. We now explore whether CNCs-β-CD can potentially evoke any inflammatory response in order to confirm its suitability as a nanodrug delivery vector.…”
Section: Cncs-β-cd Does Not Induce a Strong Immunologicalmentioning
confidence: 96%
See 1 more Smart Citation
“…Nanoparticle surface coatings can impact both cytotoxicity and immunogenicity of nanosized biomedical materials [33]. We recently showed that CNCs-β-CD was not cytotoxic to mouse monocyte cells (J774A.1) and human breast adenocarcinoma cells (MCF-7) [21]. We now explore whether CNCs-β-CD can potentially evoke any inflammatory response in order to confirm its suitability as a nanodrug delivery vector.…”
Section: Cncs-β-cd Does Not Induce a Strong Immunologicalmentioning
confidence: 96%
“…Given the wide potential therapeutic applications of CNCs in addition to their needle-like morphological features, a thorough understanding of the interaction of CNCs with the biological system is crucial for investigating any possible associated health risks. From a toxicological point of view, several studies have shown that pristine CNCs, fluorescently labeled CNCs, and surface-modified CNCs exhibited low cytotoxicity under the conditions tested with various cell lines or aquatic species [16][17][18][19][20][21][22]. While cytotoxicity assessment is the first crucial step in determining the suitability of a material for biomedical applications, further detailed investigation of any potential immunological response is also recommended [12].…”
Section: Introductionmentioning
confidence: 99%
“…159 Organic coatings of CNCs can have an effect on carrier cytotoxicity. 160 CNCs modified with polymers of various natures in comparison with bare CNCs on J774A.1 and MCF-7 cell lines have been tested. The results indicated that cells exposed to surface coated CNCs for 24 h did not show major changes in cell viability, membrane permeability, and cell morphology.…”
Section: Cellulose-based Materialsmentioning
confidence: 99%
“…The hydroxyl groups in the cellulose backbone (Figure 1 ) can react with different molecules through esterification, etherification and oxidation, affording derivatives with excellent properties (Medronho et al, 2013 ; Qiu and Hu, 2013 ; Zhang et al, 2013 ; Liu et al, 2015a ; Mogosanu and Grumezescu, 2015 ; Thakur, 2015 ; Lalatsa and Barbu, 2016 ; Ndong Ntoutoume et al, 2016 ; Umoren and Eduok, 2016 ; Jawaid and Mohammad, 2017 ; Jimenez et al, 2017 ; Sun et al, 2017b ).…”
Section: Why Using Cellulose and Cyclodextrin Derivatives?mentioning
confidence: 99%
“…Cyclodextrins (CDs) and cellulose are fascinating molecules with synergistic properties that have been critical for preparing new derivatives directed at several innovative applications, ranging from textiles (El Ghoul et al, 2016 ; Mihailiasa et al, 2016 ) coatings (Huang et al, 2013 ; Shah et al, 2015 ; Mihailiasa et al, 2016 ; Umoren and Eduok, 2016 ; Jimenez et al, 2017 ), sensors (Qiu and Hu, 2013 ) and paper making to pharmaceutical technology (Siepmann and Peppas, 2001 ; Hadjichristidis et al, 2003 ; Zhang et al, 2012 ; Shokri and Adibkia, 2013 ; Yang and Yang, 2013 ; Mogosanu and Grumezescu, 2015 ; Thakur, 2015 ; Lalatsa and Barbu, 2016 ; Jawaid and Mohammad, 2017 ; Nishio et al, 2017 ; Yadav et al, 2018 ). Cellulose has been considered a suitable matrix for preparing polymers containing CDs.…”
Section: Introductionmentioning
confidence: 99%